The incidence of the literature courses on the students learning process in the Foreign Language Department at the University of El Salvador. - Romero Morán, Gilberto Antonio
There is plenty of information about the Eglish teaching and English learning practice available around the world. There are also many sources of information as scholars who have written books in English as a second language teaching. Still, we, English language students, do have the need for data sources which answer specific questions concerning our educational contexts. The following research was developed with the specific objective of becoming a source of information for future ESL teachers and students who will deal with the necessity of having studies conducted about their peers and partners on the road to good English language teaching and English language learning. This investigation deals with the inclusion of literature topics and literature materials in English language teaching in the majors of “Licenciatura en Idioma Inglés” and “Licenciatura en Lenguas Modernas” syllabuses and curriculum designs in the Foreign Language Department at the University of El Salvador. It took a year and a half to collect, analyze and conclude on the many data that appear in the following pages. Moreover, it took the collaboration of many sources whose insights and points of views are presented here. This work also is meant to be a startintg point for further research on the topics that appear on this investigation and by no means pretends to have the ultimate truth about our research topic but to pave the way for the next generation of researchers interested in continuing this work.